Modification of nutritional value during storage of infant formulas elaborated with different intact and partially hydrolyzed proteins and carbohydrates (2015)
ABSTRACT: Background: Human milk is considered the best source of nutrition for young infants. However, if mothers cannot provide adequate breast milk or if infants are premature or have a low birth weight, breast-feeding must often be replaced or complemented with infant formulas (IFs). The interactions between infant formula components (proteins, fats, carbohydrates, vitamin and minerals) mainly affect carbohydrates and proteins (Maillard reaction, MR), but those involving proteins are especially important in products used in infant feeding because of the high protein requirements of infants. On the other hand, fatty acids (FAs) are considered important in infant development. Objectives: The aim of the present work was to test the stability of IFs made with different ingredients, analyzing the available lysine losses (for protein stability) and the FAs content and the peroxide value (for fat stability) during stored at normal and adverse conditions and to propose a faster control of that stability. Methods: Available lysine analyzed by high-performance liquid chromatography (HPLC), lipid oxidation by titrimetric method and FAs profile by gas chromatography (GC) were determined in four types of IFs prepared with intact and partially hydrolyzed proteins and different carbohydrates (lactose or maltodextrins) during storage at 4, 20 and 30 ºC for 24 months at normal water activity (Aw=0.1-0.4), and at Aw of 0.65 at 20 and 30 ºC for 4 weeks. These IFs were prepared twice (IF1 and IF2) in different batches by a Spanish dietary product company. Results: At 30ºC, available lysine losses were 40-50% in all IFs analyzed. The behavior and percentage lysine loss between 1 and 4 weeks of storage at 30 °C with Aw=0.65 was similar to those obtained after 24 months of storage at 30 °C. No significant changes were observed in fatty acid profile during storage. Oxidation was only observed in opened packs and after 4 weeks/30 °C/Aw=0.65. Conclusions: The losses of available lysine increase to higher time and storage temperatures. The FAs shows a good stability for any storage condition; however peroxide values prove more sensitive than FAs changes for evaluating fat oxidation during the storage of IFs.